Orang Benar akan Hidup Oleh Iman Menurut Roma 1:16-17 - Lontoh, Royke (Sekolah Tinggi Teologi Adhi Wacana Surabaya, 2023)
ABSTRACT This research aims to provide an explanation and arguments that salvation is a grace through the Gospel, and this grace is attained when individuals have faith in the Lord Jesus. Furthermore, faith in the Lord Jesus will lead each individual to live in righteousness. By utilizing the method of exegesis to extract meaning from Romans 1:16-17, the response has been acquired that the Gospel is the pathway to salvation for all. Belief in Jesus through the Gospel has guided individuals towards a new life, which is to receive the gift of salvation. Faith in Jesus directs the chosen people of God towards a righteous life and engages them in a continuous process of living in truth.